2022
DOI: 10.3389/ijph.2022.1605419
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Solid Fuel Use and Non-Neoplastic Digestive System Diseases: A Population-Based Cohort Study Among Chinese Middle-Aged and Older Population

Abstract: Objectives: We tended to explore the association of indoor air pollution (IAP) and non-neoplastic digestive system diseases (NNDSD) among the Chinese middle-aged and older population.Methods: From 2011 to 2018, we included 7884 NNDSD-free adults from the China Health and Retirement Longitudinal Study (CHARLS). Physician-diagnosed NNDSD was obtained by self-reported information at baseline and updated across follow-up surveys. We investigated the associations between baseline exposure of solid fuel use for cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Although the survey has emphasized the need for participants to report diseases based on previous doctors’ diagnoses, it is undeniable that there may be bias. Due to the data limitations of CHARLS, previous studies ( 49 , 50 ) have also used digestive diseases assessment methods consistent with this study, and have emphasized the limitations of self-reported bias and measurement bias. However, on the other side, given the scarcity of primary medical resources, if the risk of sarcopenia in middle-aged and older adults after 4 years can be determined based on self-reported digestive diseases, this may be of great value for early intervention and prevention of sarcopenia, as self-reported digestive diseases are very easy to obtain and do not require accurate medical equipment diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Although the survey has emphasized the need for participants to report diseases based on previous doctors’ diagnoses, it is undeniable that there may be bias. Due to the data limitations of CHARLS, previous studies ( 49 , 50 ) have also used digestive diseases assessment methods consistent with this study, and have emphasized the limitations of self-reported bias and measurement bias. However, on the other side, given the scarcity of primary medical resources, if the risk of sarcopenia in middle-aged and older adults after 4 years can be determined based on self-reported digestive diseases, this may be of great value for early intervention and prevention of sarcopenia, as self-reported digestive diseases are very easy to obtain and do not require accurate medical equipment diagnosis.…”
Section: Discussionmentioning
confidence: 97%